Study of Probability-Time Characteristics of GSM Standard Mobile Telecommunication Networks - Hasanov, M.H.; Mammadov, F.H.; Sultanova, S.A.; Israfilova, Q.A. (Herald of Azerbaijan Engineering Academy, 2023)
GSM standard mobile telecommunication networks are analyzed, their simplified physical model and vector models of these networks are developed based on it. Analytical models of these networks and methods for calculating probability-time characteristics is proposed based on the M/M/1 type singlechannel mass service system, which includes Poisson flow, exponential service time and unlimited queue. Numerical values of the probability-time characteristics such as the probability of the length of the queue in the system, the average number of requests and its average stay time in the system, the average waiting time of all requests in the queue, as well as the fully normalized average value of the stay time of requests in the system are calculated and analyzed through the conducted experiments.